Reviews (Modern theology, 1996)
Book reviewed in this article: Remembering the Christian Past by Robert L. Wilken Exbodying Forgiveness: A Theological Analysis by L. Gregory Jones Boundaries of Our Habitations: Tradition and Theological Construction by Delwin Brown Theological Essays II by Eberhard Jüngel, ed. John Webster, trans. Arnold Neufeldt-Fast and John Webster (Edinburgh: T. & T. Clark, 1994); and, The Possibilities of Theology: Studies in the Theology of Eberhard Jüngel in his Sixtieth Year, ed. John Webster